2016
DOI: 10.1021/acssynbio.5b00216
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium glutamicum Metabolic Engineering with CRISPR Interference (CRISPRi)

Abstract: Corynebacterium glutamicum is an important organism for the industrial production of amino acids. Metabolic pathways in this organism are usually engineered by conventional methods such as homologous recombination, which depends on rare double-crossover events. To facilitate the mapping of gene expression levels to metabolic outputs, we applied CRISPR interference (CRISPRi) technology using deactivated Cas9 (dCas9) to repress genes in C. glutamicum. We then determined the effects of target repression on amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
150
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(157 citation statements)
references
References 64 publications
(117 reference statements)
1
150
0
Order By: Relevance
“…A significant level of repression of ␤-galactosidase expression via CRISPRi was reported in E. coli in which dCas9 and a lacZ-targeting gRNA were maintained in plasmids (29). In the same study, up to 300-fold repression of expression of a monomeric red fluorescent protein (mRFP) was observed, which is similar to the CRISPR-dCas9-mediated RFP repression levels achieved in Corynebacterium glutamicum (39). The differences in repression efficiency observed between ␤-galactosidase and RFP suggests that certain targets may be more susceptible to CRISPRi.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…A significant level of repression of ␤-galactosidase expression via CRISPRi was reported in E. coli in which dCas9 and a lacZ-targeting gRNA were maintained in plasmids (29). In the same study, up to 300-fold repression of expression of a monomeric red fluorescent protein (mRFP) was observed, which is similar to the CRISPR-dCas9-mediated RFP repression levels achieved in Corynebacterium glutamicum (39). The differences in repression efficiency observed between ␤-galactosidase and RFP suggests that certain targets may be more susceptible to CRISPRi.…”
supporting
confidence: 59%
“…On the other hand, CRISPRi provides excellent transcriptional control and is simple to implement in many organisms. The CRISPRdCas9 system has been applied to genome-scale transcriptional repression (35) and activation (35,36) for interrogation of gene function in human cell lines as well as to genetic and metabolic engineering of Escherichia coli (37,38), Corynebacterium glutamicum (39), and mycobacteria (40).…”
mentioning
confidence: 99%
“…Moreover, the deletion of pck and pyk genes, results in an accumulation of Lglutamate through an enhanced flux of oxaloacetate in the TCA cycle, due to the absence of the transformation of oxaloacetate to phospoenolpyruvate. They demonstrated that final L-lysine and L-glutamate yields obtained with the reduced expression of pgi, pck, and pyk genes are comparable to the one obtained by gene deletion (Cleto et al, 2016). Therefore CRISPRi represents a quick and efficient solution to modify the pathway without complex gene deletions or mutations (Dominguez et al, 2016).…”
Section: Novel Approachesmentioning
confidence: 96%
“…One of the most innovative procedures is the engineering of new enzymes, such as glyceraldehyde 3-phosphate dehydrogenase (GAPDH), which can produce 2 moles of NADPH from 1 moles of glucose (Bommareddy et al, 2014) leading to a higher yield of the target amino acid. Moreover, innovative approaches utilizing CRISPR interference (CRISPRi) to modify quickly and efficiently the metabolic pathway without gene deletions and mutation has been recently developed (Cleto et al, 2016) (see section 3.2.7 for more details).…”
Section: Strain Improvementmentioning
confidence: 99%
See 1 more Smart Citation